Fractionation of a tumor-initiating UV dose introduces DNA damage-retaining cells in hairless mouse skin and renders subsequent TPA-promoted tumors non-regressing - van de Glind, Gerline (Oncotarget, 2016)
Sunburns and especially sub-sunburn chronic UV exposure are associated with increased risk of squamous cell carcinomas (SCCs). Here we focus on a possible difference in tumor initiation from a single severe-sunburn dose (on day 1, 21 hairless mice) and from an equal dose fractionated into very low sub-sunburn doses not causing any (growth-promoting) epidermal hyperplasia (40 days daily exposure, n=20). From day 47 all mice received 12-O-Tetradecanoylphorbol-13-acetate (TPA) applications (2x/wk) for 20 weeks to promote tumor development within the lifetime of the animals. After the sub-sunburn regimen sparse DNA damage-retaining basal cells (quiescent stem cells, QSCs) remained in the non-hyperplastic epidermis. These cells were forced to divide by TPA. After discontinuation of TPA tumors regressed and disappeared in the ‘sunburn group’ but persisted and grew in the ‘sub-sunburn group’ (0.06 vs 2.50 SCCs and precursors ≥4mm/mouse after 280 days, p=0.03). As the tumors carried no mutations in p53, H/K/N-Ras and Notch1/2, these ‘usual suspects' were not involved in the UV-driven tumor initiation. Although we could not selectively eliminate QSCs (unknown phenotype) to establish causality, our data suggest that forcing specifically DNA damage-retaining QSCs to divide – with high mutagenic risk - gives rise to persisting (mainly ‘in situ’) skin carcinomas.